PERANCANGAN PETA DIGITAL RUTE PATROLI BERBASIS GOOGLE MY MAPS SEBAGAI DATA DUKUNG DASHBOARD ROADMAP PATROLI MAUNG PRESISI POLDA BANTEN - Babay Suhendri; Iwan Muri Susanto; Widyawati Widyawati (LPPM Unbaja, 2026)
Polda Banten faces significant challenges in monitoring patrol effectiveness across a vast and heterogeneous jurisdiction, ranging from densely populated residential areas and industrial zones to strategic toll roads such as the Tangerang-Merak Toll Road. The limited real-time visual supervision regarding personnel compliance in following designated patrol routes remains a primary obstacle in suppressing crime rates, specifically Curat (theft with force), Curas (theft with violence), and Curanmor (motor vehicle theft). This research aims to design digital patrol route maps using the Google My Maps platform as the primary database supporting the Maung Presisi Patrol Roadmap Dashboard. The research method employed is descriptive qualitative with a systems engineering approach, involving the processing of spatial data from the 2025-2026 Patrol Roadmap document. The research phases include identifying 95 priority routes, determining geographic coordinates (geocoding), and digitizing these routes into layers based on Regional Units (Satwil), such as Serang Kota, Cilegon, and Tangerang Selatan. The result of this study is an integrated digital map prototype containing detailed street information, route lengths, and vulnerability classifications. The integration of Google My Maps into the dashboard enables leadership to monitor personnel movement precisely and compare field realization with operational work plans. The conclusion of this study indicates that the transformation from a conventional roadmap to a digital-based one enhances personnel accountability, facilitates leadership supervision, and optimizes the police's preventive response to security disturbances in real-time. The implementation of this technology is expected to serve as a model for efficient public security management in the Police 4.0 era